Aurelia de Souza: um genio a brincar as escondidas - Matos, Rodolfo (2019)
We  aim to show in this article a possible way to obtain conjectures that can serve as starting points  for further research using very similar methods  to those that can be  used  to  carry  out  cyber  attacks,  by  extracting  information   from  digital footprint  on   the  Internet   of  a  target,  even  without   using  social  engineering (S.a., n.d.-m), following previous work (Matos & Morais, 2018).Using  information-extraction  methodologies    from  images   and   applying   cold reading  methods   (S.a.,   n.d.-s),   hot  reading  (S.a.,  n.d.-o)   and   reading  body language (S.a., n.d.) to analyze  the characters and self-portraits of some works by Aurelia de Souza, in this article we present an hypothesis of deconstruction of these same works.The eighteen  (18)  conjectures obtained  allow us to suggest that  Aurelia de Souza uses  combinations  of  colors  and   objects,  such   as  symbols,   to  send   hidden messages (conjecture  1).  Likewise,  the  disposition  of the  characters she  paints, their expression,  and  the  place I object to  which  they  are looking  at  may  have certain meanings and not have been made in a random  way (conjectures 2 and 4). As such, this  exercise seems  to reveal that  the  content  of the  works  analyzed  is essentially  of a  political nature,  from  which  one could  surmise  that  the  author could be a republican sympathizer (conjectures 3 , 6, 7 and 8).